RELIGION BEYOND RELIGIONS IN NIETZSCHE - Njarakunnel, George (Journal of Dharma, 1980)
Nietzsche is one of those few thinkers who have excited such a wider range of conflicting interests, sordid and spiritual, shallow and profound. To the conventional, a satanic mind-clothed in the abominations of Anti-Christ and deserving secretive bad end. To the progressive a prophet and philosopher of the future.' His philosophy is very relevant to our times. Nietzsche does not require much of an introduction to the present. He speaks directly within it. His problems are our problems too. So a concern with his philosophy is not only a matter of intellectual curiosity but an existential necessity as well.